SYIAH: SEJARAH TIMBUL DAN PERKEMBANGANNYA DI INDONESIA - Moh. Hasim (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2012)
Syiah has become a new problem in Indonesia, eventhough it has been hundreds years existing. The the way of treating toward Syiah has been in kind a violence to freedom of religion. It needs to trace how the history emerging of this school of religion in Indonesia. By library research, and critical approach, this research finds that the Syiah teachings is based on Sayidina Ali (4th Khalifa) and his descendants. Syiah has been developed becoming many sects since there are differences on appointment of religious leader or imam. There are four stages of Syiah development in Indonesia, the first together with entering Islam in Indonesia. The second, after Iran revolution. The third, brought by Indonesia students who studied in Iran. And the fourth, disseminating by the organization ‘Ikatan Jamaah Ahlul Bait Indonesia`.